Complete genome sequencing and comparative phylogenomics of nine African swine fever virus (ASFV) isolates of the virulent East African p72 genotype IX without viral sequence enrichment - Domelevo Entfellner, Jean-Baka; Okoth, Edward A.; Onzere, C.K.; Upton, C.; Njau, E.P.; Höper, D.; Henson, Sonal P.; Oyola, Samuel O.; Bochere, Edwina; Machuka, Eunice M.; Bishop, Richard P. (MDPI, 2024)
African swine fever virus (ASFV) is endemic to African wild pigs (Phacochoerus and Potamochoerus), in which viral infection is asymptomatic, and Ornithodoros soft ticks. However, ASFV causes a lethal disease in Eurasian domestic pigs (Sus scrofa). While Sub-Saharan Africa is believed to be the original home of ASFV, publicly available whole-genome ASFV sequences show a strong bias towards p72 Genotypes I and II, which are responsible for domestic pig pandemics outside Africa. To reduce this bias, we hereby describe nine novel East African complete genomes in p72 Genotype IX and present the phylogenetic analysis of all 16 available Genotype IX genomes compared with other ASFV p72 clades. We also document genome-level differences between one specific novel Genotype IX genome sequence (KE/2013/Busia.3) and a wild boar cell-passaged derivative. The Genotype IX genomes clustered with the five available Genotype X genomes. By contrast, Genotype IX and X genomes were strongly phylogenetically differentiated from all other ASFV genomes. The p72 gene region, on which the p72-based virus detection primers are derived, contains consistent SNPs in Genotype IX, potentially resulting in reduced sensitivity of detection. In addition to the abovementioned cell-adapted variant, eight novel ASFV Genotype IX genomes were determined: five from viruses passaged once in primary porcine peripheral blood monocytes and three generated from DNA isolated directly from field-sampled kidney tissues. Based on this methodological simplification, genome sequencing of ASFV field isolates should become increasingly routine and result in a rapid expansion of knowledge pertaining to the diversity of African ASFV at the whole-genome level.